Pemetaan Kesesuaian Lahan untuk Pengembangan Tanaman Kelapa Sawit di Kebun Percobaan Fakultas Pertanian Lokasi Gelumbang - Jaya Priatna, Satria; Prayitno, Muh Bambang (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Priatna SJ, Prayitno MB, 2022. Mapping of land suitability for developmentoil palm plants in experimental land Faculty of Agriculture location of Gelumbang. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 596-606. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Faculty of Agriculture, Sriwijaya University plans to carry out re-planting activities by converting rubber plants to oil palm. For this reason, information on soil fertility conditions and the level of suitability of the land if it is used as oil palm is needed. This study aims to determine the land suitability class (actual and potential) and the condition of soil fertility. This research was conducted using a detailed survey method, where the minimum distance for sampling is ±100 meters at a depth of 0 - 40 cm. While the evaluation of land suitability is carried out using the matching system method between the results of field observations and laboratory tests with the conditions for growing oil palm plants. The results showed that the experimental garden of FP Unsri Gelumbang had an actual suitability class which was classified as less suitable for planting oil palm (S3) with the main limiting factors being low nutrient availability (N, P & K), very acidic soil pH and low CEC value, However, potentially, if the limiting factor is improved, then the land can change its suitability class to Limited Suitability (S2) to Suitable (S1).